2008
DOI: 10.1039/b810978h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective regulation of a metal complex in reversible binding to serum albumin: dynamic helicity inversion signalled by circularly polarised luminescence

Abstract: The helicity of the (SSS)-Delta enantiomer of a terbium and europium(III) complex is inverted on reversible binding to 'drug site II' of serum albumin, signalled by a switch in its circularly polarised emission; no such behaviour occurs with the (RRR)-Lambda complexes, thereby defining a unique chiroptical probe of albumin binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 31 publications
(4 reference statements)
2
61
0
Order By: Relevance
“…Similarly the luminescence dissymmetry factor g lum (Table 1, S4 and S5) increases with concentration reaching a high g lum value of -0.45 for [Eu(R-Phbipox) 2 ](OTf) and +0.45 for [Eu(S-Phbipox) 2 ](OTf) at the Eu( 5 D 0 → 7 F 1 ) transition at 6 mM which is among the highest reported for chiral complexes of europium. 3,9,34 This increase parallels the formation of the homochiral trinuclear assemblies ΛΛΛ-[Eu(R-Phbipox) 2 ] 3 +3 ΔΔΔ-[Eu(S-Phbipox) 2 ] 3 +3 at high concentrations of the [Eu(R-Phbipox) 2 ](OTf) and [Eu(S-Phbipox) 2 ](OTf) complexes in acetonitrile. 30 In 1 mM acetonitrile solutions, where only the monomeric complexes are present, a g lum value of less than 0.10 was measured.…”
mentioning
confidence: 82%
“…Similarly the luminescence dissymmetry factor g lum (Table 1, S4 and S5) increases with concentration reaching a high g lum value of -0.45 for [Eu(R-Phbipox) 2 ](OTf) and +0.45 for [Eu(S-Phbipox) 2 ](OTf) at the Eu( 5 D 0 → 7 F 1 ) transition at 6 mM which is among the highest reported for chiral complexes of europium. 3,9,34 This increase parallels the formation of the homochiral trinuclear assemblies ΛΛΛ-[Eu(R-Phbipox) 2 ] 3 +3 ΔΔΔ-[Eu(S-Phbipox) 2 ] 3 +3 at high concentrations of the [Eu(R-Phbipox) 2 ](OTf) and [Eu(S-Phbipox) 2 ](OTf) complexes in acetonitrile. 30 In 1 mM acetonitrile solutions, where only the monomeric complexes are present, a g lum value of less than 0.10 was measured.…”
mentioning
confidence: 82%
“…Since most of these studies have already been summarized numerous times in the literature,9–11,19,20,48,84,85 this section, devoted to the work performed in the research laboratory of Parker, focuses on new results based on the sensing of proteins. A recent work performed by Montgomery et al resulted in the discovery of a very unique chiroptical probe for serum albumin binding 86. They showed that the Δ-conformer of the Ln(III) complexes with the enantiopure ligand ( SSS )- 1 (Fig.…”
Section: Survey Of Luminescent Chiral Ln(iii) Complexes As Potentiamentioning
confidence: 99%
“…133 Whilst no significant change in In a later publication, distinct similarity was noted between the CPL spectral form of…”
Section: Sensing Through a Change In Complex Configurationmentioning
confidence: 99%